'Bartlett' pear fruit (Pyrus communis L.) ripening regulation by low temperatures involves genes associated with jasmonic acid, cold response, and transcription factors - Nham, Ngoc T (Plant science : an international journal of experimental plant biology, 2017)
Published by Elsevier B.V.